Can the MIT App Inventor® application be integrated into soil protection strategies? - CIORUȚA, Bogdan-Vasile; COMAN, Mirela (Technium Sustainability, 2022)
This paper starts from the definition, descriptive characterization, and analysis of the MIT App Inventor® platform, according to the users' perceptions, to emphasize the malleability of the platform to the digital consumer society demands. The analysis of how the App Inventor® can be implemented in soil protection strategies is done in conjunction with the configuration of a digital field agenda. The analysis was conducted in the Office of Informatics, from October 2020 to December 2021, and involved identifying and scoring the elements that can make App Inventor® used to create specific soil protection apps. The analysis methodology included the main components of mobile devices that may be related to the acquisition and processing of field data (camera, video, navigation, map, and other sensors). As a result of the configuration and pre-testing of the application, it was observed that the App Inventor® can be used successfully in soils monitoring and protection.